The Legal Standing Of Public Accountant Audit Results As A Basis For Determining State Losses: An Analysis Of The Medan District Court Decision Number 58/Pid.Sus.TPK/2022/PN.Mdn. - Herman Harahap; Surya Perdana; Andryan (CERED Indonesia Institute, 2025)
The determination of state financial losses is a fundamental element in corruption law enforcement. Current judicial practice indicates a tendency among law enforcement officials to utilize public accountant audit results as the primary basis for establishing the element of state losses, which constitutionally falls within the domain of authority of the Audit Board of Indonesia (Badan Pemeriksa Keuangan - BPK). This study aims to dogmatically analyze the legal standing of public accountant audit results within the administrative law system and to examine the juridical implications of their use as an evidentiary instrument through an examination of the Medan District Court Decision Number 58/Pid.Sus.TPK/2022/PN.Mdn. This study employs a normative juridical method with a statutory approach (statute approach) and a case approach (case approach). The findings conclude that from an administrative law perspective, public accountants lack attribution, delegation, or mandate authority to issue state administrative decisions. Public accountant audit results are characterized by reasonable assurance, which is subject to a professional standards regime rather than constituting final legal truth. The utilization of public accountant opinions as the basis for determining state losses by the court in the a quo decision constitutes a category error that reduces the principles of legal governance to the supremacy of technical expertise. Furthermore, the analysis of trial facts and the Constitutional Court Decision Number 003/PUU-IV/2006 demonstrates a failure to disentangle the causality of criminal liability, which proportionately results in a distortion of the application of substantive criminal law against private legal subjects.